Pendidik Dan Pengembangan Kurikulum Di MI/SD - Putri Sa’adah Siregar; Ahmad Sarkawi Efendi; Alyatun Nazmi; Zunidar Zunidar (Jurnal Sains, Teknik, Ekonomi, dan Pendidikan, 2026)
Educators and curriculum are two fundamental components that determine the success of educational implementation in Madrasah Ibtidaiyah (MI) and Elementary Schools (SD). Educators not only serve as learning practitioners but also as curriculum developers who are responsible for adapting the learning process to students’ needs. This study aims to describe the concept of educators and curriculum development in MI/SD, analyze the role of educators in curriculum development, and examine the competencies that educators must possess to support curriculum development. The study employs a qualitative approach using library research. Data were collected through documentation studies of books, scientific journals, and relevant legislation, and then analyzed using content analysis techniques. The findings indicate that educators play strategic roles as curriculum implementers, developers, facilitators, and evaluators. The success of curriculum development is strongly influenced by educators’ pedagogical, personal, social, and professional competencies. Furthermore, a continuously developed curriculum supported by competent educators can create effective, innovative, and student-centered learning that aligns with students’ developmental needs. Therefore, improving the quality of educators is a crucial factor in supporting successful curriculum development and enhancing the quality of education in MI/SD.